2019
DOI: 10.4274/btdmjb.galenos.2018.20180621103019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Group Aerobic Training on Menstrual Cycle Symptoms in Primary Dysmenorrhea

Abstract: Amaç: Primer dismenore, kadınlarda en sık görülen jinekolojik sorunlardan birisidir ancak alternatif başa çıkma yöntemleriyle ilgili kanıtlar yeterli değildir. Bu çalışmanın amacı primer dismenoresi olan kadınlarda dört haftalık aerobik eğitim programının premenstrüel semptomlar, menstrüel semptomlar, emosyonel durum ve yaşam kalitesi üzerine etkinliğini araştırmaktı. Yöntemler: Katılımcılar randomize olarak aerobik egzersiz grubuna (AEG) (n=18) ve kontrol grubuna (KG) (n=19) ayrıldı. AEG, dört hafta boyunca h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 14 publications
1
8
0
9
Order By: Relevance
“…Moreover, exactly half of the studied students had a duration of menstrual bleeding ranged from 6-7 days. This finding is aligned with Akbas E (2019) (25) who demonstrated that the mean duration of menstruation was 6.10±0.87. Also, the current study revealed that less than two thirds of both the study and the control groups had moderate menstrual flow (2-3 pads/day).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, exactly half of the studied students had a duration of menstrual bleeding ranged from 6-7 days. This finding is aligned with Akbas E (2019) (25) who demonstrated that the mean duration of menstruation was 6.10±0.87. Also, the current study revealed that less than two thirds of both the study and the control groups had moderate menstrual flow (2-3 pads/day).…”
Section: Discussionsupporting
confidence: 88%
“…Pada penelitian Ortiz, dkk [16] dan Dehnavi, dkk [4] terdapat penurunan intensitas dismenorea pada wanita dismenorea yang melakukan olahraga dengan frekuensi tiga kali perminggu selama empat minggu, sedangkan penelitian Vaziri, dkk [17] dan Akbas Eda, dkk [18] menyatakan olahraga dapat menurunkan intensitas dismenorea primer dalam waktu delapan minggu. Keempat penelitian ini menunjukan terdapat penurunan intensitas dismenorea primer dalam jangka waktu yang berbeda.…”
Section: A Pendahuluanunclassified
“…In the study (Akbas and Erdem, 2019) 14 37 women aged 18 to 25 who experienced primary dysmenorrhea were divided into two groups, namely the aerobic exercise group and the control group. The treatments were carried out three times a week for four weeks.…”
Section: Aerobic Exercise Reduces Primary Dysmenorrheamentioning
confidence: 99%